Cochrane Review: Screening programmes for developmental dysplasia of the hip in newborn infants. Issue 1 (9th January 2013) - Shorter, Damon; Hong, Timothy; Osborn, David A
Abstract Background Uncorrected developmental dysplasia of the hip (DDH) is associated with long term morbidity such as gait abnormalities, chronic pain and degenerative arthritis. Objectives To determine the effect of different screening programmes for DDH on the incidence of late presentation of congenital hip dislocation. Search methods Searches were performed in CENTRAL (The Cochrane Library), MEDLINE and EMBASE (January 2011) supplemented by searches of clinical trial registries, conference proceedings, cross references and contacting expert informants. Selection criteria Randomised, quasi‐randomised or cluster trials comparing the effectiveness of screening programmes for DDH. Data collection and analysis Three independent review authors assessed study eligibility and quality, and extracted data. Main results No study examined the effect of screening (clinical and/or ultrasound) and early treatment versus not screening and later treatment. One study reported universal ultrasound compared to clinical examination alone did not result in a significant reduction in late diagnosed DDH or surgery but was associated with a significant increase in treatment. One study reported targeted ultrasound compared to clinical examination alone did not result in a significant reduction in late diagnosed DDH or surgery, with no significant difference in rate of treatment. Meta‐analysis of two studies found universal ultrasound compared to targeted ultrasound did not result in a significant reduction in late diagnosed DDH or surgery. There was heterogeneity between studies reporting the effect on treatment rate. Meta‐analysis of two studies found delayed ultrasound and targeted splinting compared to immediate splinting of infants with unstable (but not dislocated) hips resulted in no significant difference in the rate of late diagnosed DDH. Both studies reported a significant reduction in treatment with use of delayed ultrasound and targeted splinting. One study reported delayed ultrasound and targeted splinting compared to immediate splinting of infants with mild hip dysplasia on ultrasound resulted in no significant difference in late diagnosed DDH but a significant reduction in treatment. No infants in either group received surgery. Authors' conclusions There is insufficient evidence to give clear recommendations for practice. There is inconsistent evidence that universal ultrasound results in a significant increase in treatment compared to the use of targeted ultrasound or clinical examination alone. Neither of the ultrasound strategies have been demonstrated to improve clinical outcomes including late diagnosed DDH and surgery. The studies are substantially underpowered to detect significant differences in the uncommon event of late detected DDH or surgery. For infants with unstable hips or mildly dysplastic hips, use of delayed ultrasound and targeted splinting reduces treatment without significantly increasing the rate of late diagnosed DDH or surgery. Plain Language Summary Screening methods for dislocated or improperly formed hips in newborn infants The hip joint is a ball and socket joint. Newborns may have hips that are not in their socket (dislocated) or hips that are improperly formed (dysplasia). Risk factors for hip dysplasia include a family history of a similar problem and female infants delivered in the breech position. The hips of most newborns will be examined clinically after birth and during infancy to determine whether they are stable, unstable or dislocated. Screening for hip dysplasia may prevent the need for late treatment, which is associated with long term hip deformity, gait disturbance and arthritis. However, early screening leads to increased treatment. Treatment may be complicated by damage to the hip due to impairment of the blood supply (avascular necrosis). This review found no studies that compared the benefits and costs of early screening versus not screening for hip problems. Studies that compared the addition of ultrasound to clinical examination reported that when ultrasound was performed on all infants, the rate of treatment increased with no significant difference in rate of late detected dysplasia or surgery. Targeted ultrasound to infants at high risk of hip dysplasia did not significantly increase the rate of treatment but also did not significantly reduce the rate of late detected dysplasia or surgery. It is not possible to give clear recommendations for hip screening of newborn infants from the available evidence. Where infants are clinically detected as having unstable but not dislocated hips, or are detected on ultrasound to have mild hip dysplasia, there is evidence that delaying treatment by two to eight weeks reduces the need for treatment without a significant increase in late diagnosed dysplasia or surgery.